DETERMINAN RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Cahyani, Dwi Indri; Dewi, Nurmila; Rusydi, Rusydi (Ekonis: Jurnal Ekonomi dan Bisnis, 2024)
Abstract: Stock return is the rate of profit obtained from an investment, which can influence investors in making investment decisions. Investors are interested in investing in companies that provide a rate of return that meets their expectations. The purpose of this research is to test and analyze the determinants of stock returns in companies listed on the Jakarta Islamic Index for the period 2018-2022. The independent variables used are the Current Ratio, Debt to Equity Ratio, and Return on Equity, while the dependent variable is Stock Return. There are 50 companies in the population listed in the Jakarta Islamic Index. The sampling technique obtained using purposive sampling consists of 13 samples. This research uses the multiple linear regression analysis method with panel data. The results show that the Current Ratio has a significant effect on stock returns, while the Debt to Equity Ratio and Return on Equity do not have a significant effect on stock returns. The contribution of all independent variables (Current Ratio, Debt to Equity Ratio, and Return on Equity) to stock returns is 57%, while 43% can be explained by other variables outside this research. Keywords: Current Ratio, Debt to Equity Ratio, Return on Equity, and Stock Return.